2023
DOI: 10.3390/ijms24043441
|View full text |Cite
|
Sign up to set email alerts
|

Tumor Mutational Burden for Predicting Prognosis and Therapy Outcome of Hepatocellular Carcinoma

Abstract: Hepatocellular carcinoma (HCC), the primary hepatic malignancy, represents the second-highest cause of cancer-related death worldwide. Many efforts have been devoted to finding novel biomarkers for predicting both patients’ survival and the outcome of pharmacological treatments, with a particular focus on immunotherapy. In this regard, recent studies have focused on unravelling the role of tumor mutational burden (TMB), i.e., the total number of mutations per coding area of a tumor genome, to ascertain whether… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(13 citation statements)
references
References 149 publications
(165 reference statements)
0
12
1
Order By: Relevance
“…6 F). TMB serves as an indicator of mutation counts in cancer [ 22 ]. A higher TMB increases self-neoantigens and immunogenic recognition, enhancing the likelihood of T cell recognition, facilitating T cell responses against tumor cells, and indicating improved outcomes with ICI [ 23 ].…”
Section: Resultsmentioning
confidence: 99%
“…6 F). TMB serves as an indicator of mutation counts in cancer [ 22 ]. A higher TMB increases self-neoantigens and immunogenic recognition, enhancing the likelihood of T cell recognition, facilitating T cell responses against tumor cells, and indicating improved outcomes with ICI [ 23 ].…”
Section: Resultsmentioning
confidence: 99%
“…4 F). Mutations associated with detrimental biological behavior were more abundant in the high-risk group than in the low-risk group, such as TP53 (36% vs. 24%), a well-known anti-oncogene that is one of the most frequently mutated genes in HCC specimens, and DOCK2 (9% vs. 3%), a mediator of cytokinesis 21 . According to the genomic characteristics of HCC mutations obtained from the previous study, we noted significant differences in the aspects of SNV neoantigens, fraction altered, aneuploidy score, and homologous recombination defects between the two groups (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Research has shown that a high TMB has been associated with a better ICI response in several solid tumor types [93][94][95]. However, this association is not consistent in HCC [96].…”
Section: Resistance Mechanisms To Icis In Hcc and Possible Solutionsmentioning
confidence: 98%